The Dynamics of Role Conflict and Time Management among Couples in Dual Earner Families - Noor Huda; Imey Ilsa Nur Afifah; Chintya Rosa Meilia; Putri Safridina Az-Zahra (The Future of Education Journal, 2026)
This study examines the dynamics of role conflict and time management among dual-earner couples, with a particular focus on the tension between professional responsibilities and child-rearing. Using a phenomenological approach and semi-structured interviews guided by Bowen's Family Systems Theory, the study was conducted with three families in the Kudus–Jepara region of Indonesia. Data were collected through in-depth interviews with six participants (three married couples) and analyzed using inductive thematic analysis. The findings revealed three major themes: (1) an imbalance in time allocation between work and family responsibilities, (2) disruption of the parent–child subsystem due to limited time for caregiving, and (3) diverse family coping strategies, ranging from role negotiation between spouses to the involvement of extended family members in childcare. These findings underscore the importance of flexible work arrangements and effective spousal communication in maintaining healthy family functioning. The theoretical and practical implications of the findings are discussed within the framework of Family Systems Theory.